2019
DOI: 10.1016/j.bpj.2019.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy Study of Curvature-Mediated Lipid Packing and Sorting in Single Lipid Vesicles

Abstract: Cellular plasma membrane deformability and stability is important in a range of biological processes. Changes in local curvature of the membrane affect the lateral movement of lipids, affecting the biophysical properties of the membrane. An integrated holographic optical tweezers and Raman microscope was used to investigate the effect of curvature gradients induced by optically stretching individual giant unilamellar vesicles (GUVs) on lipid packing and lateral segregation of cholesterol in the bilayer. The sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
(65 reference statements)
1
11
0
Order By: Relevance
“…Therefore, RTM, with a typical processing capacity of 0.2 particles per min, is not considered a high-throughput methodology 71 . RTM can, however, be used to obtain interesting, unique information not only for EVs 57,60,61,[70][71][72][73][74][75][76][77] but also for many other bioparticles such as liposomes, lipid layers on synthetic nanoparticles and others [78][79][80][81][82][83] .…”
Section: Label-free Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, RTM, with a typical processing capacity of 0.2 particles per min, is not considered a high-throughput methodology 71 . RTM can, however, be used to obtain interesting, unique information not only for EVs 57,60,61,[70][71][72][73][74][75][76][77] but also for many other bioparticles such as liposomes, lipid layers on synthetic nanoparticles and others [78][79][80][81][82][83] .…”
Section: Label-free Methodologiesmentioning
confidence: 99%
“…Direct visualization of EVs using microscopy lets researchers assess the shape and size of vesicles in their native state 156 and in various biological processes 157 , while other techniques, such as RTM, can be employed to examine further the morphology of bioparticles without direct visualization. For example, the effect of membrane lipid composition on the shape and size of giant unilamellar vesicles was first described using Raman tweezers, demonstrating that a decrease in cholesterol concentration increases the local membrane curvature and stretches the vesicle 82 .…”
Section: Ev Characterizationmentioning
confidence: 99%
“…23 Also, it was reported that the apparent ratio I aCH /I sCH can slightly decrease with temperature increase, when the lipids are in a liquid-like state, and it can be changed with the vesicle deformation. 24,25 This complicates the analysis if only information about I aCH is used. On the other hand, a comparison of the expectation for I aCH , calculated in the spirit of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4,9,10 RACS in flow can be both non-invasive and have higher throughput than methods that rely on measuring spectra of cells that are (momentarily or permanently) stationary, followed by cell picking. Since spontaneous Raman spectra are often inherently weak, to date, most of the methods that have used cells in microfluidic systems have used a "trapand-release" approach, employing methods such as optical tweezing 4,[11][12][13][14][15] or dielectrophoresis. 16,17 Although "cell trapping" can meet the need for long signal acquisition, ultimately the trapping mechanism limits throughput, and the efficiency of the trap is often dependent on cell size, medium conductivity, refractive index and/or flow rate.…”
Section: Introductionmentioning
confidence: 99%